2009
DOI: 10.1074/jbc.m808742200
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Facilitate Adipocyte Differentiation by Accelerating Mitotic Clonal Expansion

Abstract: Growth-arrested 3T3-L1 preadipocytes rapidly express CCAAT/enhancer-binding protein-␤ (C/EBP␤) upon hormonal induction of differentiation. However, the DNA binding activity of C/EBP␤ is not activated until the cells synchronously reenter S phase during the mitotic clonal expansion (MCE) phase of differentiation. In this period, C/EBP␤ is sequentially phosphorylated by MAPK and glycogen synthase kinase-3␤, inducing C/EBP␤ DNA binding activity and transcription of its target genes. Because the DNA binding activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
306
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 360 publications
(339 citation statements)
references
References 43 publications
26
306
0
7
Order By: Relevance
“…Labeled cells were analyzed using a FACS caliber flow cytometry system, and data were analyzed using the ModFit software (BD Biosciences) as described. 30 Cell labeling with BrdU and immunofluorescence analysis. Labeling with BrdU was done using the BrdU Labeling and Detection Kit I (Roche, Mannheim, Germany) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Labeled cells were analyzed using a FACS caliber flow cytometry system, and data were analyzed using the ModFit software (BD Biosciences) as described. 30 Cell labeling with BrdU and immunofluorescence analysis. Labeling with BrdU was done using the BrdU Labeling and Detection Kit I (Roche, Mannheim, Germany) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, both ATM and c-Abl were found to be activated not only by DNA damage induction but also by insulin treatment (20,34), suggesting a possible mechanism of c-Abl activation by adipogenic induction through ATM. It was also demonstrated that genotoxic drugs or reactive oxygen species can promote adipocyte differentiation of cultured mesenchymal progenitors of adipocytes (35,36). An intriguing possibility that should be further investigated is that controlled DNA damage is being used during normal adipogenesis to activate key regulators like c-Abl.…”
Section: Discussionmentioning
confidence: 99%
“…The 3T3-L1 preadipocytes were cultured and differentiated into adipocytes as described previously (27). Briefly, 3T3-L1 preadipocytes were maintained in DMEM containing 100 U/mL penicillin, 100 μg/mL streptomycin, and 8 μg/mL biotin, supplemented with 10% (vol/vol) heat-inactivated calf serum at 37°C, in an atmosphere of 90% air and 10% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Protein samples of equal amount were separated by SDS/ PAGE and transferred to nitrocellulose membranes. Western blot analysis was performed using the following antibodies: polyclonal antibodies against PPARγ (Cell Signaling Technology) and C/EBPα (27); and mouse monoclonal antibodies against PPARγ, β-actin (Santa Cruz Biotechnology), and FLAG (Sigma).…”
Section: Methodsmentioning
confidence: 99%